Beneficial Effect of Silicon Application and Intermittent Irrigation on Improving Rice Productivity in Indonesia - Fatmah Siregar, Adha; Ibrahim Adamy Sipahutar; Husnain; Masunaga, Tsugiyuki (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2020)
It is believed that silicon (Si) application could increase rice production, however studies related to those topics are still limited. The study determined the combination effect of Si application and water management on rice growth and productivity. This study was conducted at the experimental station of Indonesian Agricultural Environment Research Institute, Jakenan, Pati, Central Java at dry season. A split-plot in randomized complete block design with four replications was set. The main plots were different types of irrigation and subplots were Si fertilizer application. Results showed that the application of Si increased plant resistance on blast disease. This current result might be due to the increasing of Si concentration in leaves. IT water management significantly increased the yield compared to CF. IT increased root growth and gave an impact on increasing of plant growth and rice yield. Moreover, IT significantly increased Cu, Mn, and Zn concentration in rice grain. Combination of Si application with IT water management could increase rice plant productivity especially in area with water shortage.Keywords: blast disease, lodging, rice productivity, silicon application, water management